2013
DOI: 10.1071/an12265
|View full text |Cite
|
Sign up to set email alerts
|

Selection of experimental treatments, methods used and evolution of management guidelines for comparing and measuring three grazed farmlet systems

Abstract: Abstract. The Cicerone Project was a collaborative effort by livestock producers, researchers and extension specialists, which aimed to explore the profitability and sustainability of grazing enterprises on the Northern Tablelands of New South Wales, Australia. A major part of the Project was the creation of a moderate scale, unreplicated farmlet experiment. The process of selecting the farmlet treatments and the design of the experiment involved considerable negotiation over an extended period in order to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…On the first of these points, the graze periods on farmlet C were typically less than 5-10 days (Hinch et al 2013a;Scott et al 2013a) and tended to be longer in winter and shorter in summer. Under optimal conditions of temperature and moisture, first development of T. colubriformis and H. contortus eggs to the infective L 3 stage in faeces takes 3 and 4 days, respectively (Hsu and Levine 1977) with appearance on herbage at Days 5 and 6, respectively (Cheah and Rajamanickam 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the first of these points, the graze periods on farmlet C were typically less than 5-10 days (Hinch et al 2013a;Scott et al 2013a) and tended to be longer in winter and shorter in summer. Under optimal conditions of temperature and moisture, first development of T. colubriformis and H. contortus eggs to the infective L 3 stage in faeces takes 3 and 4 days, respectively (Hsu and Levine 1977) with appearance on herbage at Days 5 and 6, respectively (Cheah and Rajamanickam 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The weather experienced during the trial period was mostly drier than average with more severe frost in winter than average (Behrendt et al 2013). The farmlet experiment commenced on 1 July 2000 following the subdivision of the three farmlets, each of 53 ha, which were managed under three different management systems described in detail by Scott et al (2013b). Stock was first introduced just before the start date and the experiment was completed by the end of 2006.…”
Section: Experimental Design and Locationmentioning
confidence: 99%
“…The farmlets were each 53 ha in size thus providing the 'credible' scale sought by livestock producer members. The farmlet treatments have been described in detail by Scott et al (2013d) while the results have been reported in several related papers in this Special Issue.…”
Section: Introductionmentioning
confidence: 99%
“…This reflected the desire by all participants to see objective evidence from comparisons rather than rely on the claims made by proponents of various, more prescriptive systems (Scott et al 2013d). In addition, the livestock producers wanted investigations to take into account the risk of adopting different technologies compared with their traditional practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation